Tracks of youth labor and educational migration: overview of preferences (Хабаршы. Психология және социология сериясы, 2025)
The purpose of the study is to review the key areas of youth migration in Kazakhstan. Youth migration goes beyond the traditional understanding of mobility, reflecting not only socio-economic differences between regions and countries, but also the formation of sustainable migration trajectories that affect the structure of national human capital.Methodology: the research employed comparative analysis, descriptive statistics, and content analysis to explore current trends in youth migration.The originality of the study lies in identifying a dual structure of migration mobility, expressed in the discrepancy between declared preferences and actual migration decisions. A shift in migration preferences of young people has been revealed from traditional destinations (Russia, the USA, Turkey) to countries with stable legal mechanisms for labor and educational mobility, such as South Korea, Germany, and the United Kingdom. Similar trends can be traced in educational migration.The results of the study generally emphasize the need to move from a migration deterrence strategy to a managed mobility concept focused on return, knowledge transfer, and institutional support for youth migration trajectories. In the context of global competition for human capital, Kazakhstan needs to form a proactive migration policy based on an analysis of the motives, barriers and opportunities for youth mobility.The value of the data obtained lies in identifying the youth's demand for security in professional self-realization, stability of legal status and predictability of career trajectories. Special attention should be paid to the "revolutionary" factor of the GenZ generation, which strives for changes in the structure of work and career models, reflecting the need for rapid adaptation to new conditions. The practical significance of the work lies in the fact that the results can be used to develop measures aimed at ensuring the safety of young people's career paths, as well as creating a flexible labor relations system that takes into account the needs and demands of the new generation.Keywords: youth migration, Kazakhstan, internal and external tracks, human capital, managed mobility, return migration.